A study of technical efficiency of main production activities of the Greek agricultural sector - Ρεζίτης Αντώνιος Ν.; Μυγδάκος Ευθύμιος; Φωτόπουλος Χρήστος (SPOUDAI Journal of Economics and Business, 2004)
This paper measures the degree of technical efficiency of main production activities of the Greek agricultural sector for the period 1989-1995. Technical efficiency measures are obtained within the framework of the stochastic frontier production function of Battese and Coelli (1995) using data of the Farm Accountancy Data Network (FAND) surveys of the period 1989-1995. Factors showing a positive effect on technical efficiency are: economic size, age of the head of the farm, family work on the farm, irrigated area, liabilities, profitability of own assets. Subsidies have a negative effect on efficiency while rental land does not have any significant effect. The average level of technical efficiency of all production activities is 87.40% indicating that there is a potential increase of agricultural output by 12.60%, given the existing level of inputs. The results indicate that the production activity with the highest average efficiency is that of wine (98.28%) followed by olive crops (97.24%), grain (96.91%), other arable crops (95.47%), multi-cultivation (93.71%), horticulture (90.63%), viticulture (85.89%), tobacco (73.99%), citrus trees and fruits (71.41%), and cotton (70.44%). JEL Classification: Q10, Q12, Q16, Q19